2022
DOI: 10.3390/ijerph192416839
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity Patterns and Their Association with Social Determinants, Mental and Physical Health during the COVID-19 Pandemic

Abstract: Background: The challenge posed by multimorbidity makes it necessary to look at new forms of prevention, a fact that has become heightened in the context of the pandemic. We designed a questionnaire to detect multimorbidity patterns in people over 50 and to associate these patterns with mental and physical health, COVID-19, and possible social inequalities. Methods: This was an observational study conducted through a telephone interview. The sample size was 1592 individuals with multimorbidity. We use Latent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…have complex needs and impose increasing demands on primary care services given the ageing population. Multimorbidity is associated with reduced life expectancy [7], lower quality of life [8] and an increased risk of hospitalisation and death with COVID-19 [9]. In clinical trials, vaccination against COVID-19 showed reduced risk of hospitalisation and death in all groups [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…have complex needs and impose increasing demands on primary care services given the ageing population. Multimorbidity is associated with reduced life expectancy [7], lower quality of life [8] and an increased risk of hospitalisation and death with COVID-19 [9]. In clinical trials, vaccination against COVID-19 showed reduced risk of hospitalisation and death in all groups [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, considering that previous studies does not provide a clear description of either the social mechanisms or the ecological effects involved in the association between the local area of residence and multimorbidity patterns, the need for studies that address the social context in which multimorbidity emerges and reproduces itself is evident 22,23 . Despite the growing recognition of multimorbidity as a public health concern, there remains to be more clarity surrounding the social mechanisms and ecological effects that contribute to the emergence and persistence of specific multimorbidity patterns.…”
mentioning
confidence: 99%